Impacts of Furrow Irrigation on Shesher and Welala Natural Reservoirs of Lake Tana Sub Basin, Ethiopia - Dereje Tewabe (International Journal of Aquaculture and Fishery Sciences - Peertechz Publications, 2014)
The survey was conducted from March 2012 to March 2013 based on field observations and samples. Shesher is natural reservoir of Lake Tana found at coordinates of 0350300 and  1322162 UTM and at altitudes 1805 a.s.l. Welala natural reservoir is found at UTM coordinates of 0348348 and 1326081 with altitude of 1804 a.s.l. The area of Shesher and Welala was estimated about 500 ha and 110 ha respectively, which are impounded by open water for extended period of a year and both with maximum depth of 3 m during rainy season. Both reservoirs filled their capacity during the rainy season through the inflow river of Ribb and the surrounding flood plain. But during pick dry season of March, 2012 and March 2013 the survey showed unexpected, amazing and sudden death of a home for many biodiversity that both Shesher and Welala natural reservoirs dried up totally. Birds fetch their food from remnants small shrink wet mud spot and it is not uncommon to see remnant dead fishes eaten by birds. This is due to several and unlimited human encroachments mainly for crop cultivation, with out any rules and regulations. Major crops cultivated by drained two reservoirs using gravitational force were Eragrastis teff, Cheak pea, Grass pea, Lentils and Safflower. During dry season no one could be able found drinking water even for their animals and humans, inhabitants started digging well to fetch water from the middle of Shesher and Welala reservoirs. The drainage system was carried out at every 50 m intervals by making large furrows in both sides of two reservoirs until their water totally vanished. These reservoirs should be properly and sustainably exploited by designing appropriate interventions with out land use change, for instance it could be serve for fisheries, ecotourism and livestock sectors.